2013
DOI: 10.4085/1062-6050-48.2.14
|View full text |Cite
|
Sign up to set email alerts
|

Lower Extremity Muscle Strength After Anterior Cruciate Ligament Injury and Reconstruction

Abstract: Arbor. Dr Thomas is now with the Department of Kinesiology, University of Toledo, OH.Context: Quadriceps and hamstrings weakness occurs frequently after anterior cruciate ligament (ACL) injury and reconstruction. Evidence suggests that knee injury may precipitate hip and ankle muscle weakness, but few data support this contention after ACL injury and reconstruction.Objective: To determine if hip, knee, and ankle muscle weakness present after ACL injury and after rehabilitation for ACL reconstruction.Design: Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
65
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(73 citation statements)
references
References 24 publications
5
65
0
3
Order By: Relevance
“…The present systematic review revealed that some recent studies reported deficits in hip strength after ACL reconstruction [18,26,36,43,62,74]. These findings may also have relevance regarding the re-rupture rate.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…The present systematic review revealed that some recent studies reported deficits in hip strength after ACL reconstruction [18,26,36,43,62,74]. These findings may also have relevance regarding the re-rupture rate.…”
Section: Discussionmentioning
confidence: 68%
“…These articles are summarized in Table 1. Four articles with a follow-up between 6 and 24 months show postoperative reduction of hip extension strength [18,26,36,74]. One study showed that the ratio of hip and knee extensors was significantly greater after ACL reconstruction 1 3 with a significant negative correlation between the hip extensor:knee extensor torque ratios and maximal anterior tibia shear [62].…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…[3][4][5] These situations are thought to be due to a compensating mechanism to prevent anterior subluxation of the tibia, [6][7][8] which can be painful and potentially detrimental to injured knees with ACL tears. 9,10 Theoretically, the reverse situation (increased quadriceps and decreased hamstring muscle strength) could be expected in patients with posterior cruciate ligament (PCL) tears to lessen the posterior subluxation of the tibia. It remains unclear, however, whether the strength of the quadriceps and hamstring increases or decreases after tears of the PCL.…”
mentioning
confidence: 99%